(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To analyze results of strabismus patient surgical treatment, which preoperatively were examined using method of automated analysis of diagnostic gaze position pictures (AADGP) and volume of subsequent surgeries was planned in three-dimensional biomechanical eye model (TBEM). Materials and methods. Preoperative diagnostic algorithm for surgery planning included automated analysis of diagnostic gaze position pictures + three-dimensional biomechanical eye model in main group. Surgery volume was planned based on conventional diagnostic tests in the 1st group of controls. Surgery volume was planned based on conventional diagnostic tests + three-dimensional biomechanical eye model in the 2nd group of controls. Patient follow-up was 6–12 months after surgery. Results. In concomitant strabismus patients orthotropy after surgery was present in 40/48 patients in main group (83,3 %), 80/120 patients in 1st group of controls (66,7 %) and 63/106 patients in 2nd group of controls (59,4 %) — РMG-CG1 = 0,09; MG-CG2 = 0,01. At 6–12 month follow-up orthtropy preserved in 43/48 patients in main group (89,6 %), 62/91 patients in 1st group of controls (68,1 %) and 53/88 patients in 2nd group of controls (60,2 %) — РMG-CG1 = 0,03; РMG-CG2 = 0,001. In strabismus with vertical deviation patients orthotropy after surgery was present in 6/8 patients in main group (75 %) and 19/30 patients in 1st group of controls (63,3 %) — РMG-CG1 = 0,54. At 6–12 month follow-up orthtropy preserved in 7/8 patients in main group (87,5 %) and 13/19 patients in 1st group of controls (68,4 %) — РMG-CG1 = 0,3. Conclusion. Developed method of automated analysis of extraocular muscle function in combination with surgery modeling in three-dimensional biomechanical eye model simplified and objectified examination of deviation angle and ocular motility in strabismus patients. It led to improvement of surgery results in these patients.